PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAYUNTUK MENINGKATKAN HASIL BELAJAR IPASISWA KELAS IV MI AL-MUHAJIRIN MENGGALA SAKTI - Musniah '; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the low of students’ result in IPA subject in class IV of MI Al-Muhajirin Menggala Sakti by range in level 56.04 by KKM 70. This problem caused the teacher do not use variation model or strategy in learning process, finally student do not active in learning. This research is Class action research. The purpose of this research is to increase the students’ learning result of IPA in class IV of MI Al-Muhajirin Menggala Sakti. The formulation of this research is “Do the Implementation of Cooperative Learning Result of IPA in Class Type Two Stay Two Stray (TSTS) Can Increase the Students’ Learning Result of IPA in Class IV of MI Al-muhajirin Menggala Sakti?”. The subject of this research is all of the students in class IV totally 24 students by note 17 students are male and 7 students are famale. The result of this research show that in basic csore is only 8 students are clear (33.33%). In cycle I the score increase in 70.00% by 17 students ant then, in cycle II the score increase in 95.00% by 23 students. The data can get conclusion that the Implementatin of Cooperative Learning Model type Two Stay Two Stray (TSTS) can increase the Students’ Learning result of IPA in class IV of MI Al-Muhajirin Menggalala sakti. Key Words: Learning model Cooperative Two Stay Two Stray (TSTS), Students’ Learning result IPA